Professional skills and competencies of a marketing specialist - Mykhailova, М. S. (ТДАТУ, 2019)
Competence is the most important quality of a specialist. It is a significant factor for achieving high results in their professional activity, using the knowledge, skills, experience and personal qualities, as well as the ability to constantly improve their own creative potential.
Keywords: marketing; marketer; competence